Scanning tunnelling microscope light emission: Finite temperature current noise and over cut-off emission - Vijith Kalathingal (Nature Portfolio, 2017)
Abstract The spectral distribution of light emitted from a scanning tunnelling microscope junction not only bears its intrinsic plasmonic signature but is also imprinted with the characteristics of optical frequency fluc- tuations of the tunnel current. Experimental spectra from gold-gold tunnel junctions are presented that show a strong bias (V b ) dependence, curiously with emission at energies higher than the quantum cut-off (eV b ); a component that decays monotonically with increasing bias. The spectral evolution is explained by developing a theoretical model for the power spectral density of tunnel current fluctuations, incorporating finite temperature contribution through consideration of the quantum transport in the system. Notably, the observed decay of the over cut-off emission is found to be critically associated with, and well explained in terms of the variation in junction conductance with V b . The investigation highlights the scope of plasmon-mediated light emission as a unique probe of high frequency fluctuations in electronic systems that are fundamental to the electrical generation and control of plasmons.